Effectiveness of Trichoderma and Mycorrhiza for Chili (Capsicum annuum L.) Growth at Jambi Agricultural Training Center - Nurhayati, Nurhayati; Fitria, Shahen Maudy; Nafiah, Rofiatun; Amanda, Ghina Tri; Asra, Revis (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Chili (Capsicum annuum L.) is one of the important horticultural crops cultivated commercially. To overcome the problem of declining soil fertility and attacks of plant disrupting organisms (OPT) which have an impact on the low growth and production of chili. This study aims to see the effect of Trichoderma sp and mycorrhiza on the growth of chili plants (Capsicum annuum L.) This study used a complete randomized design (CRD) with 3 treatments and 10 replications. The treatments given are P0 = no treatment (control), P1 = Trichoderma sp, P2 = Mycorrhiza and P3 = Trichoderma sp - mycorrhiza. The parameters observed included plant height (cm) and number of leaves (strands) which were observed once a week for four observations. The research data were analyzed using analysis of variance (ANOVA) at the 5% error level and if there was a real effect, further tests were carried out with DMRT (Duncan's Multipe Range Test). The results of the study on average plant height and number of leaves obtained from observations of 15 HST, 22 HST, 29 HST and 36 HST the highest was P1, namely treatment with Trichoderma sp gave good results on the growth of chili plants. The implications of this research can provide data and non-data regarding the results of the effectiveness test of trichoderma and mycorrhiza applications on the growth of chili plants.